From point to pixel a genealogy of digital aesthetics - Hoy, Meredith (Hanover, New Hampshire Dartmouth College Press, 2017)
In this fiercely ambitious study, Meredith Anne Hoy seeks to reestablish the very definitions of digital art and aesthetics in art history. She begins by problematizing the notion of digital aesthetics, tracing the nineteenth- and twentieth-century movements that sought to break art down into its constituent elements, which in many ways predicted and paved the way for our acceptance of digital art.

Through a series of case studies, Hoy questions the separation between analog and digital art and finds that while there may be sensual and experiential differences, they fall within the same technological categories. She also discusses computational art, in which the sole act of creation is the building of a self-generating algorithm. The medium isn't the message—what really matters is the degree to which the viewer can sense a creative hand in the art.
Keywords: Digital images; Art -- Philosophy